Formation of Magmatic Fe-Ti-V-P Deposits Within the Lac St. Jean Area Saguenay, Québec, Canada: Insights from Trace Element Composition of Fe-Oxides and Apatite - Grant, Mark (Université d'Ottawa / University of Ottawa, 2020)
The Lac St. Jean area in the Grenville Province of Quebec contains abundant anorthosite-hosted Fe-Ti-V and Fe-Ti-P mineralization comprised of massive to semi-massive Fe-oxides (magnetite ± ilmenite ± Al-spinel) and nelsonite (~2/3 oxide, ~1/3 apatite), respectively. Currently, information regarding regional-scale variation of mineralization, with respect to the composition of Fe-oxides, their relationship with host rocks, and genesis of the mineralization (i.e. immiscibility of a Fe-Ti ± P-rich magma vs. fractional crystallization) are not well constrained. In order to gain information into these enigmatic deposits, modern techniques involving in-situ laser ablation (LA)-ICP-MS analysis of Fe-oxides and apatite at the University of Ottawa combined with detailed petrography and whole rock lithogeochemistry were applied to samples from mineralization and host anorthosites from 2 Fe-Ti-V and 4 Fe-Ti-P deposits/occurrences. Results show that magnetite from Fe-Ti-P mineralization has a more evolved composition relative to magnetite from Fe-Ti-V mineralization. However, observed differences in; 1) relative abundance of Fe-oxide phases, 2) Fe-oxide exsolution textures, 3) visible corona-forming reactions with co-existing silicate phases (when present), and 4) whole rock compositions of corresponding massive oxide samples indicate possible post cumulus changes on primary composition of magnetite within each deposit/occurrence in this study. Post-cumulus processes appear to have a limited effect on the primary magmatic composition of apatite. Therefore, apatite appeared to be a robust indicator of primary magmatic compositions and was used to describe differences regarding the compositions of parental magma and oxygen fugacity (fO₂) conditions among the Fe-Ti-P deposits/occurrences. This study shows that, when combined with detailed petrography and whole rock lithogeochemistry, in-situ trace element composition of Fe-oxide minerals and apatite is a reliable indicator of the physiochemical conditions of the magmas which formed Fe-Ti-V and Fe-Ti-P mineralization within the Lac St. Jean area.
Keywords: Geology; Economic Geology